SISTEM INFORMASI GEOGRAFIS (GIS) PENDISTRIBUSIAN DAGING QURBAN BERBASIS APLIKASI WEB - Indra Maulana Yusup Kusumah; Mida Tsamrotul Hamidah; Linda Apriyanti (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2020)
Every year in the event of sacrificial animal slaughter on the Eid al-Adha Day, there is inequality between one region and another. In addition, the lack of coordination between qurban animal committees, so that in certain locations there can be excess or shortage of qurban meat stocks. Therefore the application of geographic information systems (GIS) distribution of web-based qurban meat is an attempt to manage the distribution of qurban meat. The information system used in this study is the application of GIS-based distribution of qurban meat with the help of Google Maps API. The application is used to distribute qurban meat at the nearest location. Not only that, in this application there are also features to complement the system to be built. Like, displaying location information, location map visualization integrated with Google Maps to display location directions. This application is based on a web application that can only be opened in a web browser. This system is made with PHP and Mysql programming languages ​​as database management. The existence of this system is expected to help the distribution process of qurban meat evenly. Keywords: Geographic Information System (GIS), Distribution, Qurban Meat, WEB Application, Google Maps Fire.